Intra and Extra-granular Disintegrant Properties of Modified Underutilised Red Lima Bean Starch in Paracetamol Tablet Formulation (2020)
Red lima bean (Phaseolus lunatus Linn) Family Fabaceae, has been modified by succinylation and annealing, and used as intra- and extra-granular disintegrants at concentrations of 5 and 10 %w/w in paracetamol tablet formulation in comparison with corn starch BP. The starches were characterised using FT-IR spectroscopy, SEM, proximate analysis, physicochemical and functional properties. FT-IR spectrometry revealed characteristic peaks at 1575.53 and 1713.99 cm-1 for the succinylated starch while the annealed showed no significant difference from the native starch. Modifications did not alter the ovoid shape of the native starch but reduced the particle size. Succinylation improved water absorption capacity, solubility and swelling of lima bean starch but annealing reduced the parameters. Tablets with disintegrants of lima bean starches generally had higher crushing strengths and lower friability than tablets with corn starch. Modifications reduced the disintegration time of the tablets when the starcheswere incorporated intra-granularly, which suggested particle-particle bond interruption and destruction of hydrogen bonds as mechanism of disintegration. Tablets containing 10 %w/w succinylated red lima bean starch incorporated intra-granularly had the highest disintegration efficiency ratio, DER, indicating a great balance between mechanical and disintegration properties. Modified red lima bean starches incorporated intra-granularly into paracetamol ablets led to faster disintegration and could efficiently substitute corn starch as disintegrant.